Salmonella Exhibit Altered Cellular Localization in the Presence of HLA-B27 and Codistribute with Endo-Reticular Membrane - Janos Kriston-Vizi; Izabela Lenart; Takao Iwawaki; Keith Gould; Darren Nesbeth; Simon J. Powis; Antony N. Antoniou (Journal of Immunology Research)
Salmonella enteritica (S. enteritica) induce and require unfolded protein response (UPR) pathways for intracellular replication. Salmonella infections can lead to reactive arthritis (ReA), which can exhibit associations with Human Leucocyte Antigen (HLA)-B∗27 : 05. S. enteritica normally reside in a juxtanuclear position to the Golgi apparatus, representing the formation and residence within the Salmonella-containing vacuole (SCV). Changes in cellular localization of infecting Salmonella can alter their ability to replicate. We therefore used isogenic epithelial cell lines expressing physiological levels of HLA-B∗27 : 05 heavy chain (HC) and a control HLA-B allele, HLA-B∗35 : 01.HC to determine any changes in Salmonella localization within epithelial cells. Expression of HLA-B∗27 : 05 but not HLA-B∗35 : 01 was associated with a quantifiable change in S. enteritica cellular distribution away from the Golgi apparatus. Furthermore, the Salmonella requirements for UPR induction and the consequences of the concomitant endoplasmic reticulum (ER) membrane expansion were determined. Using confocal imaging, S. enteritica bacteria exhibited a significant and quantifiable codistribution with endo-reticular membrane as determined by ER tracker staining. Isogenic S. enterica Typhimurium mutant strains, which can infect but exhibit impaired intracellular growth, demonstrated that the activation of the UPR was dependent on an integral intracellular niche. Therefore, these data identify cellular changes accompanying Salmonella induction of the UPR and in the presence of HLA-B27.